2011
DOI: 10.1007/s11524-011-9552-y
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemic in Evolution: The Need for New Models of HIV Care in the Chronic Disease Era

Abstract: Since the beginning of the AIDS epidemic, models of HIV care have needed to be invented or modified as the needs of patients and communities evolved. Early in the epidemic, primary care and palliative care predominated; subsequently, the emergence of effective therapy for HIV infection led to further specialization and a focus on increasingly complex antiretroviral therapy as the cornerstone of effective HIV care. Over the past decade, factors including (1) an aging, long-surviving population; (2) multiple co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 48 publications
(37 reference statements)
3
111
0
2
Order By: Relevance
“…Now, with refinement of more effective, better tolerated, less toxic ART, 12 HIV has a better prognosis and been transformed into a chronic condition in which comorbidity management is central. 13,14 This is especially the case as HIV-infected patients age; 64 % of Veterans with HIV in VA are over age 50 and increasingly have aging-associated comorbidities, 15 most commonly depression (51 %), hypertension (49 %), dyslipidemias (43 %), substance abuse (30 %) and diabetes (19 %). 16 Thus, care for these patients has become more about comorbidity than HIV management.…”
Section: Introductionmentioning
confidence: 99%
“…Now, with refinement of more effective, better tolerated, less toxic ART, 12 HIV has a better prognosis and been transformed into a chronic condition in which comorbidity management is central. 13,14 This is especially the case as HIV-infected patients age; 64 % of Veterans with HIV in VA are over age 50 and increasingly have aging-associated comorbidities, 15 most commonly depression (51 %), hypertension (49 %), dyslipidemias (43 %), substance abuse (30 %) and diabetes (19 %). 16 Thus, care for these patients has become more about comorbidity than HIV management.…”
Section: Introductionmentioning
confidence: 99%
“…19,40 Sixteen percent of HIV patients in Ontario receive care exclusively from family physicians with lower HIV experience; our results suggest potential disparities in ART among these patients. Because we also found that this influence of family physician HIV experience is mitigated by having an HIV specialist within their model of care, in order to ensure adequate ART prescribing, care delivery models for people with HIV should include either an HIV specialist or a family physician with considerable HIV experience.…”
Section: Discussionmentioning
confidence: 75%
“…[10][11][12][13][14][15][16][17][18] There is increasing recognition that the management of HIV requires a primary care presence, but we have a poor understanding of how to integrate HIV-specific expertise within a primary care context. 7,10,[14][15][16][17][18][19][20][21] Overall, it has been difficult to distinguish the respective contributions of physician qualification and physician experience of care to the effectiveness of HIV care. 3 We have previously used routinely collected administrative data to develop and characterize an intuitive typology of shared care for people with HIV based on actual patterns of care.…”
Section: Introductionmentioning
confidence: 99%
“…12,31,32 This phenomenon may be related in part to the time constraints associated with the management of HIV and associated comorbidities. 33,34 These findings have implications for HIV care practice and policy, which must increasingly encompass the prevention and management of comorbidities across the lifespan and requires communication and integration across primary and specialist care. 33,35 …”
Section: Resultsmentioning
confidence: 99%
“…33,34 These findings have implications for HIV care practice and policy, which must increasingly encompass the prevention and management of comorbidities across the lifespan and requires communication and integration across primary and specialist care. 33,35 …”
Section: Resultsmentioning
confidence: 99%